Impact of tobacco tax reforms on tobacco prices and tobacco use in Australia. (23rd July 2003) - Scollo, M; Younie, S; Wakefield, M; Freeman, J; Icasiano, F
Abstract : Objective: To document the impact of changes to tobacco taxes on the range and price of tobacco sold during the period when the National Tobacco Campaign (NTC) was run. Data sources: Information about brand availability, pack size, and price was extracted from Australian Retail Tobacconist . A retail observational survey was undertaken to monitor actual retail prices. Data on cigarette prices, brands, packet configurations, and outlets from which they were purchased were obtained from the benchmark and three follow up population telephone surveys conducted to evaluate the NTC. Method: Data from the three sources were compared to see the extent to which the impact of tax changes had been offset by greater retail discounting and a more concerted effort by consumers to purchase cheaper products. Results: Smokers were unable to cushion themselves from the sharp price increases that occurred during the third phase of the NTC. Both average recommended retail prices of manufactured cigarettes and average actual cigarette prices paid by smokers increased by 25% in real prices. Conclusion: The fall in smoking prevalence over the first two phases of the NTC was substantially greater than would be expected due to tax changes alone. The fall in smoking consumption over the first two phases was slightly less than would be expected and in the third considerably higher than would be expected.